Rapid Appraisal of PNPM Neighborhood Development (and Poverty Alleviation Partnership Grant Mechanism) - Schuler, Nina; Dwiyani, Risye (World Bank, Washington, DC, 2015)
The World Bank has had a long history of supporting community driven development and urban upgrading projects in Indonesia, reaching back to the 1970's. The primary approach of all program nasional pemberdayaana masyarakat (PNPM) urban projects is to provide block grants at the kelurahan level to community trusts (BKM) that work with their communities to identify, plan, and implement activities (largely infrastructure) to improve urban settlements and support poverty alleviation efforts. In 2009, the World Bank and the Government of Indonesia launched two new pilot programs to build upon the success and lessons of PNPM urban. These pilots were PNPM urban poverty alleviation partnership grant (PAPG) and PNPM urban neighborhood development (ND). To support project learning, the World Bank has commissioned this rapid appraisal of PNPM PAPG and ND with an aim to review broadly what is working, what isn t working and what improvements can be made explicitly with an aim to inform a future round of World Bank supported urban project(s) that will include a scale up of the PNPM ND approach while integrating some key elements from PAPG (a hybrid approach). It should be noted that the scaling up of PNPM urban ND has the potential to result in one of the world s largest community driven slum upgrading programs. The paper is divided into three sections. It begins with a brief overview of the study methodology. It outlines the project s design structure and key assumptions, providing an analysis of each of the main project assumptions and inputs with lessons learned from the field visits. The final section offers project specific recommendations. An extensive annex has also been provided which includes brief overviews of each of the sites visited.